Influence of Tourism Product and Service Quality On Consumer Satisfaction - Saragi, Charles Parnauli; Utami, Nisa Rahmaniyah; Azzahra, Nadira (Prasetiya Mulya Publishing, 2025)
This study examines the influence of educational tourism product quality and service quality on consumer satisfaction at PT Ekowisata Kreatif Indonesia. Superior products with unique advantages can attract consumer interest, driven by internal motivation to purchase. Understanding product and service quality is essential for tour providers to meet consumer needs and create satisfaction. Using a quantitative approach, the research involved 100 respondents determined through the Slovin formula and selected via simple random sampling. Data analysis employed the Partial Least Square (PLS) method with SmartPLS software, covering measurement models, structural models, and hypothesis testing. Findings revealed that both product quality and service quality significantly affect consumer satisfaction, with service quality showing the strongest influence. This indicates that consumers are highly satisfied with the services offered during educational tours. Overall, the study highlights that maintaining high product and service quality is crucial in enhancing consumer satisfaction within the tourism industry.